Seminal, clinical and colour‐Doppler ultrasound correlations of prostatitis‐like symptoms in males of infertile couples. (28th November 2013) - Lotti, F.; Corona, G.; Mondaini, N.; Maseroli, E.; Rossi, M.; Filimberti, E.; Noci, I.; Forti, G.; Maggi, M.
Summary 'Prostatitis‐like symptoms' (PLS) are a cluster of bothersome conditions defined as 'perineal and/or ejaculatory pain or discomfort and National Institutes of Health‐Chronic Prostatitis Symptom Index (NIH‐CPSI) pain subdomain score ≥4' (Nickel's criteria). PLS may originate from the prostate or from other portions of the male genital tract. Although PLS could be associated with 'prostatitis', they should not be confused. The NIH‐CPSI is considered the gold‐standard for assessing PLS severity. Although previous studies investigated the impact of prostatitis, vesiculitis or epididymitis on semen parameters, correlations between their related symptoms and seminal or scrotal/transrectal colour‐Doppler ultrasound (CDU) characteristics have not been carefully determined. And no previous study evaluated the CDU features of PLS in infertile men. This study was aimed at investigating possible associations among NIH‐CPSI (total and subdomain) scores and PLS, with seminal, clinical and scrotal/transrectal CDU parameters in a cohort of males of infertile couples. PLS of 400 men (35.8 ± 7.2 years) with a suspected male factor were assessed by the NIH‐CPSI. All patients underwent, during the same day, semen analysis, seminal plasma interleukin 8 (sIL‐8, a marker of male genital tract inflammation), biochemical evaluation, urine/seminal cultures, scrotal/transrectal CDU. PLS was detected in 39 (9.8%) subjects. After adjusting for age, waist and total testosterone (TT), no association among NIH‐CPSI (total or subdomain) scores or PLS and sperm parameters was observed. However, we found a positive association with current positive urine and/or seminal cultures, sIL‐8 levels and CDU features suggestive of inflammation of the epididymis, seminal vesicles, prostate, but not of the testis. The aforementioned significant associations of PLS were further confirmed by comparing PLS patients with age‐, waist‐ and TT‐matched PLS‐free patients (1 : 3 ratio). In conclusion, NIH‐CPSI scores and PLS evaluated in males of infertile couples, are not related to sperm parameters, but mainly to clinical and CDU signs of infection/inflammation.